Legalitas Perkawinan Beda Agama Menurut Undang-Undang Nomor 1 Tahun 1974 Tentang Perkawinan Dan Undang-Undang Nomor 23 Tahun 2006 Tentang Administrasi Kependudukan (JURNAL HUKUM SEHASEN, 2017)
Undang-Undang No. 1 Tahun 1974 Article 1 mentions that marriage is a bond of inner birth between a man and a woman as husband and wife in order to form a happy and eternal family (household) based on God Almighty. The article 2 clause (1) explains that legal marriage is a marriage that is done according to the law of each religion and belief. Indonesia is still prohibiting the marriage of different religions, but today the marriage of different religions is increasingly widespread. Controversy occurred when the issuance of Undang-Undang No. 23 Tahun 2006 regarding Population Administration. Due to the existence of this Act is very possible to pairs of religious differences can be recorded marriage of origin through the establishment of the Court. This is stated in Article 35 (a) which states that the marriage registration shall also apply to the marriage set by the Court. In the explanation of this article "that the marriage set by the court is a marriage performed among people of different faiths. Based on the results of the study can be concluded that the provisions of Undang-Undang No. 1 Tahun 1974 About Marriage and Compilation of Islamic Law prohibits the marriage of different religions. While the rules applicable in Article 35 letters (a) of Undang-Undang No. 23 Tahun 2006 concerning Population Administration tend to allow marriage of religious differences, resulting in a synchronization between the Marriage Law and the Population Administration Act. So in the principle of legislation apply adagium lex specialis derogat lex generalis (legislation that is specific to rule out general laws and regulations). Marriage Law is a special rule that is about marriage then the position is on lex specialis. While the Population Administration Act is general, because it concerns a general nature, not only regulate the marriage registration but also the administration of other population. So it can be said that the Marriage Law overrides the Population Administration Act, which means that the marriage of different religions is prohibited by the prevailing laws and regulations in Indonesia. This research is a descriptive analysis that describes the systematic, factual, and accurate problems studied. While the approach used is the juridical normative approach is the approach used to determine the existing laws and regulations, and review through Islamic law and positive law.Keyword: legality, marriages.